CORPORATE SOCIAL RESPONSIBILITY di PT. PRUDENTIAL LIFE ASSURANCE - Ratu Annisa Fairuz; Faachira Faachira; Santoso Tri Raharjo; Risna Resnawaty (Universitas Padjadjaran, 2018)
ABSTRACTCorporate social responsibility program activities also vary, not only limited to social and economic programs. Social, education, and environment can be the target of corporate social responsibility. One company that applies corporate social responsibility is PT. Prudential Life Assurance. PT. Prudential Life Assurance was first established in 1995. Prudential was originally Prudential Plc, a financial services group from the United Kingdom with more than 160 years of experience. By combining Prudential's international experience in the field of life insurance with knowledge of local business procedures. Prudential has been in Indonesia since 1999 and has a commitment to develop its business in Indonesia. In accordance with these three things Prudential focuses its CSR activities in the fields of education, children, and disaster relief and prevention. Through the theme of